2022
DOI: 10.1128/spectrum.00025-22
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Genomic Approach to Determine the Virulence Factors and Horizontal Gene Transfer Events of Clinical Acanthamoeba Isolates

Abstract: Acanthamoeba has the ability to cause serious blinding keratitis. Although the prevalence of this phenomenon has increased in recent years, our knowledge of the underlying opportunistic pathogenic mechanism maybe remains incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…While studied for decades, Acanthamoeba research has only recently expanded to utilize robust -omic methods to understand more about this amoeba’s dynamic lifecycle ( Bernard et al, 2022 ). Even now, limited genome annotation and no stable methods for impacting gene expression have significantly hampered Acanthamoeba research where the pathogenesis of other ocular microorganisms like Pseudomonas are well-described and the risk factors for infection clearly delineated ( Gu et al, 2022 ). Equally, the infrequent diagnosis of Acanthamoeba keratitis’ has prevented significant investment in treatment development and infection prevention, despite devastating outcomes for those affected ( Siddiqui and Khan, 2012 ; Szentmary et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While studied for decades, Acanthamoeba research has only recently expanded to utilize robust -omic methods to understand more about this amoeba’s dynamic lifecycle ( Bernard et al, 2022 ). Even now, limited genome annotation and no stable methods for impacting gene expression have significantly hampered Acanthamoeba research where the pathogenesis of other ocular microorganisms like Pseudomonas are well-described and the risk factors for infection clearly delineated ( Gu et al, 2022 ). Equally, the infrequent diagnosis of Acanthamoeba keratitis’ has prevented significant investment in treatment development and infection prevention, despite devastating outcomes for those affected ( Siddiqui and Khan, 2012 ; Szentmary et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that the adhesion of Acanthamoeba to the cornea is a crucial prerequisite for the subsequent inflammatory response and the degree of adhesion is directly proportional to the strength of the host’s inflammatory response ( Wang and Zhu, 2010 ). LBP participates in the initial phase where infiltration is limited to the corneal epithelium, particularly in the intercellular space ( Gu et al, 2022 ). Therefore, the selectivity of Acanthamoeba for the host cornea also determines the differences in the specificity of AK in different hosts.…”
Section: Acanthamoeba Related Diseasesmentioning
confidence: 99%
“…The authors reported genes coding for metalloprotease, laminin-binding protein, and heat shock proteins (HSP) and identified several endosymbionts such as species of Chlamydiae , Mycobacterium , Legionella , Burkholderia , Rickettsia, and Pseudomonas , which were significantly different among the isolated, being Pseudomonas spp. the most common bacteria shared in all strains, so they discussed the possibility that this genus may be closely related to virulence and pathogenicity; however, more studies are needed to prove this hypothesis [ 167 ].…”
Section: Advances In Genomic Epidemiologymentioning
confidence: 99%